The current clinical landscape of neonatal respiratory failure in Jiangsu Province of China: patient demographics, NICU treatment interventions, and patient outcomes - Na Wang; Ke-Yu Lu; Shan-Yu Jiang; Hong-Wei Wu; Rui Cheng; Zhao-Jun Pan; Huai-Yan Wang; on behalf of the Jiangsu Provincial Collaborative Study Group for Neonatal Respiratory Diseases (BMC, 2024)
Abstract Introduction Neonatal respiratory failure (NRF) is a serious condition that often has high mortality and morbidity, effective interventions can be delivered in the future by identifying the risk factors associated with morbidity and mortality. However, recent advances in respiratory support have improved neonatal intensive care units (NICUs) care in China. We aimed to provide an updated review of the clinical profile and outcomes of NRF in the Jiangsu province. Methods Infants treated for NRF in the NICUs of 28 hospitals between March 2019 and March 2022 were retrospectively reviewed. Data collected included baseline perinatal and neonatal parameters, NICU admission- and treatment-related data, and patient outcomes in terms of mortality, major morbidity, and survival without major morbidities. Results A total of 5548 infants with NRF were included in the study. The most common primary respiratory disorder was respiratory distress syndrome (78.5%). NRF was managed with non-invasive and invasive respiratory support in 59.8% and 14.5% of patients, respectively. The application rate of surfactant therapy was 38.5%, while that of neonatal extracorporeal membrane oxygenation therapy was 0.2%. Mortality and major morbidity rates of 8.5% and 23.2% were observed, respectively. Congenital anomalies, hypoxic-ischemic encephalopathy, invasive respiratory support only and inhaled nitric oxide therapy were found to be significantly associated with the risk of death. Among surviving infants born at < 32 weeks of gestation or with a birth weight < 1500 g, caffeine therapy and repeat mechanical ventilation were demonstrated to significantly associate with increased major morbidity risk. Conclusion Our study demonstrates the current clinical landscape of infants with NRF treated in the NICU, and, by proxy, highlights the ongoing advancements in the field of perinatal and neonatal intensive care in China.